Early Diagenesis in Sediments of the Venice Lagoon (Italy) and Its Relationship to Hypoxia - Brigolin, Daniele; Rabouille, Christophe; Demasy, Clément; Bombled, Bruno; Monvoisin, Gaël; Pastres, Roberto (Frontiers in Marine Science, 2021)
This work focuses on sediments of a shallow water lagoon, located in a densely populated area undergoing multiple stressors, with the goal of increasing the understanding of the links between diagenetic processes occurring in sediments, the dynamics of dissolved oxygen in the water column, and potential consequences of hypoxia. Sediment data were collected over three consecutive years, from 2015 to 2017, during spring-summer, at 5 stations. Measured variables included: sediment porosity, grain size and organic carbon content, porewater microprofiles of O2, pH and H2S, porewater profiles of dissolved inorganic carbon (DIC), total alkalinity (TA), NH4+, NO3-, dissolved Fe and SO42-. In addition, long-term time series of oxygen saturations in the water column (years 2005-2017) were utilized in order to identify the occurrence and duration of hypoxic periods. The results show that the median dissolved oxygen saturation value in summer months was below 50% (around 110 µmol L-1), and that saturation values below 25% (below the hypoxic threshold) can persist for more than one week. Sediment stations can be divided in two groups based on their diagenetic intensity: intense and moderate. At these two groups of stations, the average DIC net production rates, estimated trough a steady-state model (Profile) were, respectively, of 2.8 and 1.0 mmol m-2 d-1, SO42- consumption rates were respectively 1.6 and 0.4 mmol m-2 d-1, while diffusive oxygen uptake fluxes, calculated from the sediment microprofile data, were of 28.5 and 17.5 mmol m-2 d-1. At the stations characterized by intense diagenesis, total dissolved sulfide accumulated in porewaters close to the sediment-water interface, reaching values of 0.7 mM at 10 cm. Considering the typical physico-chemical summer conditions, the theoretical time required to consume oxygen down to the hypoxic level by sediment oxygen demand ranges between 5 and 18 days, in absence of mixing and re-oxygenation. This estimation highlights that sediment diagenesis may play a crucial role in triggering and maintaining hypoxia of lagoon waters during the summer season in specific high intensity diagenesis zones. This role of the sediment could be enhanced by changes in regional climate conditions, such as the increase in frequency of summer heat waves.